Developments in Undernutrition in Indian Children Under Five: A Decompositional Analysis - Peng Nie; Anu Rammohan; Wencke Gwozdz; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2016)
This study uses two waves (2004–2005 and 2011–2012) of the nationally representative Indian Human Development Survey to conduct a systematic decompositional analysis of the demographic and socio-economic factors contributing to undernutrition among children under five in India. The analytic method combines three types of decomposition: Blinder-Oaxaca, non-linear, and unconditional quantile. Child undernutrition is measured by z-scores for height-for-age (HAZ), weight-for-height (WHZ), weight-for-age (WAZ), and for the Composite Index of Anthropometric Failure (CIAF). Although our results show modest improvements on some measures, undernutrition among India's young children remains widespread. The improvements we do identify are partly attributable to changes in household wealth and maternal characteristics like body mass index and education.
Keywords: I15; I31; C21; 330; child undernutrition; India; decomposition